Front Cover: A Phos‐tag‐based micropipette‐tip method for rapid and selective enrichment of phosphopeptides. Issue 19 (4th October 2017) - Yuan, Elena Tianfei; Ino, Yoko; Kawaguchi, Maho; Kimura, Yayoi; Hirano, Hisashi; Kinoshita‐Kikuta, Emiko; Kinoshita, Eiji; Koike, Tohru
Abstract : Electrophoresis 2017, 38, 2447–2455. DOI:10.1002/elps.201700175 The cover picture shows a novel phosphate‐affinity micropipette‐tip method using Phos‐tag agarose beads. The 'Phos‐tag tip' has been designed and developed for efficient enrichment of low‐molecular‐mass phosphorylated biomolecules, such as nucleotides, phosphorylated amino acids, or phosphopeptides. The separation can be conducted by using aqueous solutions at neutral pH. The operation time from sample addition to elution is less than 30 min. This method might provide the means to perform a variety of experiments in metabolomics and phosphoproteomics by coupling with various down‐stream applications including advanced mass spectrometry‐based technology.